Differences In Communication Skills And Mathematical Problem Solving Abilities Of Students Who Are Taught Using A Jigsaw And Make Match Type Cooperative Learning Model - Harahap, Lamia (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine the differences in communication skills and mathematical problem solving abilities of students who are taught with jigsaw and make a match cooperative learning on cube and block material for class VIII MTs Nurul Islam Indonesia for the 2019-2020 school year. This research is a type of quantitative research with a quasi-experimental type of research. The population is all grade VIII students of MTs Nurul Islam Indonesia for the 2019-2020 academic year. The data analysis technique was carried out by analysis of variance (ANAVA). The results of these findings indicate: 1)The communication skills and mathematical problem solving skills of students who are taught using the jigsaw type cooperative learning model are better than students who are taught the make a match cooperative learning model. 2)The mathematical communication ability of students who are taught with the jigsaw type of cooperative learning model is better than the students who are taught by the make a match type of cooperative learning model. 3) The mathematical problem solving ability of students who are taught using the jigsaw cooperative learning model is not better than students who are taught the make a match cooperative learning model. 4) There is no significant interaction between the learning model used on students' mathematical problem solving and communication skills. The conclusions of this study explain that the communication skills and mathematical problem solving skills of students who are taught with the jigsaw type cooperative learning model are better than the make a match type cooperative learning model on the cube and block material of class VIII MTs Nurul Islam Indonesia for the 2019-2020 school year.